2022
DOI: 10.2147/dmso.s370222
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism Score for Visceral Fat (METS-VF): A New Predictive Surrogate for CKD Risk

Abstract: Purpose Metabolic disorders are closely related to the occurrence and development of chronic kidney disease (CKD). We explored the prospective association between the Metabolic Score for Visceral Fat (METS-VF) and CKD in a 5-year follow-up study. Patients and Methods In this cohort study, 631 adults not suffering from CKD from Wanzhai Town, in China in 2012 were included at baseline and followed up in 2017 and 2018. Multivariable logistic regression was used to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Carrying excess weight around the abdomen increases the likelihood of developing kidney disease ( 13 ). Adipose tissue helps maintain the equilibrium between food intake and energy expenditure through the production of adipokines under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Carrying excess weight around the abdomen increases the likelihood of developing kidney disease ( 13 ). Adipose tissue helps maintain the equilibrium between food intake and energy expenditure through the production of adipokines under normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The CVAI was established to assess visceral fat distribution in Asians and was reported to outperform the VAI in predicting renal injury [15,41]. As a composite index combining age, sex, height, weight, WC, glucose, and lipids, METS-VF was considered an excellent predictor of CKD [42]. In this study, we were delighted to observe that the NVAI had a stronger predictive power than the CVAI and the METS-VF for SRD in the Chinese population.…”
Section: Discussionmentioning
confidence: 85%
“…Huh et al [ 36 ] studied 6,065 Korean persons without CKD at baseline, and over a follow-up period of 10 years showed that insulin resistance was an independent risk factor for development of CKD. Interestingly, the study by Feng et al also found that the Metabolism Score for Visceral Fat (METS-VF) was a new indicator for predicting CKD risk, which integrated HOMA-IR, waist-to-height ratio, visceral adiposity index, and body mass index [ 37 ]. METS-VF can comprehensively evaluate the impact of abdominal adipose tissue on whole-body metabolism, and abdominal adipose tissue is one of the important sources of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%